Artistic Liberties : American Literary Realism and Graphic Illustration, 1880-1905 - Sonstegard, Adam, 1971- (Book collections on Project MUSE., 2014)
Artistic Liberties is a landmark study of the illustrations that originally accompanied now-classic works of American literary realism and the ways editors, authors, and illustrators vied for authority over the publications. Though today, we commonly read major works of nineteenth-century American literature in unillustrated paperbacks or anthologies, many of them first appeared as magazine serials, accompanied by ample illustrations that sometimes made their way into the serials' first printings as books.